III - Lacertílios da Amazônia: Os lagartos da Amazônia brasileira, com especial referência aos representados na Coleção do Museu Goeldi. - (:unkn) unknown (Museu Paraense Emilio Goeldi, 1961)
The present paper is the result of a revisional study made by Author on the collections of the Museu Goeldi, with the aim of a better classification of all the known species of the Amazonian lizards. A brief discussion of the ecology, geographical distribution and taxonomy is made. Data are presented on the different habits of the genera and of some of the species, with emphasis on their habits and behavior in the Amazon area. The last part of the paper refers to the taxonomy and description of the species represented in the museum's collections, and to the data on the biology and the distribution cf other species not present in these collections.
Keywords: Lagartos; Lacertílios; Amazônia; Coleção Herpetológica (MPEG)